Unsettling Stories : Settler Postcolonialism and the Short Story Composite. - Kuttainen, Victoria (Cambridge Scholars Pub., 2010)
The first study of the synergies between postcolonialism and the genre of the short story composite, Unsettling Stories considers how the form of the interconnected short story collection is well suited to expressing thematic aspects of postcolonial writing on settler terrain. Unique for its comparative considerations of American, Canadian, and Australian literature within the purview of postcolonial studies, this is also a considered study of the difficult place of the postcolonial settler ...